Who could that be at this hour? - Snicket, Lemony; Seth, 1962- (New York Little, Brown, 2014)
Thirteen-year-old Lemony Snicket begins his apprenticeship with S. Theodora Markson of the secretive V.F.D. in the tiny dot of a town called Stain'd By The Sea, where he helps investigate the theft of a statue.
Keywords: Apprentices -- Fiction; Statues -- Fiction; Stealing -- Fiction; Mystery and detective stories; Humorous stories